If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(2X + -4) = 40 + -5X Reorder the terms: 5(-4 + 2X) = 40 + -5X (-4 * 5 + 2X * 5) = 40 + -5X (-20 + 10X) = 40 + -5X Solving -20 + 10X = 40 + -5X Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '5X' to each side of the equation. -20 + 10X + 5X = 40 + -5X + 5X Combine like terms: 10X + 5X = 15X -20 + 15X = 40 + -5X + 5X Combine like terms: -5X + 5X = 0 -20 + 15X = 40 + 0 -20 + 15X = 40 Add '20' to each side of the equation. -20 + 20 + 15X = 40 + 20 Combine like terms: -20 + 20 = 0 0 + 15X = 40 + 20 15X = 40 + 20 Combine like terms: 40 + 20 = 60 15X = 60 Divide each side by '15'. X = 4 Simplifying X = 4
| 10x+5=-10x+25 | | 5g-18+13=g+19 | | -4=-1+k/4 | | 8x-6-3x=14 | | 14x-7=5+12x | | x^3-5x^2-14x-20=0 | | -2(-7-8n)=-82 | | T+5=t-19 | | 4k-7=21 | | 14a^5+295a^3b^2+21ab^4= | | 5.5j+8.9k-4.7k-10.9j= | | 6x+7x^13=-13 | | -(1+3a)=-36+4 | | (3x-6)-8=2 | | 20y-15x+2x+10y+21=180 | | 88=3x+4(x+8) | | 6+2k=10 | | 3y-6+4y=8 | | 6(x+3)-3(x-4)+2x=17+3-5 | | -.3x=6 | | 3y+1=6x+5 | | 3(x-6)-8=2 | | -.3=6 | | 3y-1+y+37=5+7y+35-5y | | 8y+9=6y-7 | | 8-2n=-2(n-4) | | 20y-15y+2x+10y+21=180 | | 1.2(7x-5)-(10-4.3x)= | | .5x=-5 | | 4x+20=2x+30 | | x+.3=3.3 | | x^2+8=-12-8x |